2010
DOI: 10.1017/s0950268810002530
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coxiella burnetii (Q fever) antibodies in bovine serum and bulk-milk samples

Abstract: Q fever (Coxiella burnetii) is a zoonotic disease of increasing public health importance. The objective of this study was to estimate the prevalence of, and risk factors associated with, exposure to C. burnetii in cattle in the Republic of Ireland. Bulk-tank milk samples from 290 dairy herds and 1659 sera from 332 dairy and beef herds, randomly sampled, were tested by indirect ELISA to detect antibodies to C. burnetii. In total, 37·9% of bulk-milk sample herds and 1·8% of sera (from 6·9% of herds) were antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 9 publications
8
35
1
3
Order By: Relevance
“…For humans, the main infection route is by inhalation of infected aerosols (Cutler et al, 2007;Roest et al, 2011a). It has been described previously that in 2007 the seroprevalence and DNA prevalence of C. burnetii in bovine herds in the Netherlands were 79% and 28%, respectively (Muskens et al, 2011) which was comparable to that in other western European countries (Agger et al, 2010;Ryan et al, 2011). Because it cannot be excluded that dairy cattle may transmit C. burnetii to other species, it is important to be able to take preventive measures to reduce the prevalence in cattle herds.…”
Section: Introductionmentioning
confidence: 73%
“…For humans, the main infection route is by inhalation of infected aerosols (Cutler et al, 2007;Roest et al, 2011a). It has been described previously that in 2007 the seroprevalence and DNA prevalence of C. burnetii in bovine herds in the Netherlands were 79% and 28%, respectively (Muskens et al, 2011) which was comparable to that in other western European countries (Agger et al, 2010;Ryan et al, 2011). Because it cannot be excluded that dairy cattle may transmit C. burnetii to other species, it is important to be able to take preventive measures to reduce the prevalence in cattle herds.…”
Section: Introductionmentioning
confidence: 73%
“…However, it was well below the range of 12.78 to 29.9% reported in the cattle from northern parts of country by other workers (Joshi et al, 1978;Vaidya et al, 2010), which may be attributed to the investigation of animals at household level, with not more than 3 cattle per house examined in the present study. On contrary, studies involving large cattle herd size with intensive farming practices were found to have a positive association with C. burnetii infection (McCaughey et al, 2010;Ryan et al, 2011;Paul et al, 2012;Agger & Paul, 2014;Boroduske et al, 2017). The positivity of a serum sample in both trans-PCR and ELISA points to an active cycling of the pathogen within the herd/animal, where the animals get infected and seroconverts frequently as described by other researchers (Freick et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of C. burnetii antibodies in milk and serum has been observed in Europe in recent years. For example, the following levels of seroprevalence have been reported: 79% in the Netherlands (12), 38% in Ireland (14), 67% in Northern Spain (3), 48% in Northern Ireland (10), 79% in Denmark (1), and 71% in Belgium (6). Moreover, Tilburg et al (18) showed that 76% commercially available milk samples or milk products from 28 countries contain significant amounts of C. burnetii DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted by other research centers in Europe have demonstrated that the prevalence of C. burnetii infection in ruminants, including dairy cattle, has been increasing in recent years. The seroprevalence in Europe was estimated at a range between 38% and 79% (3,6,12,14). The results of serological and molecular tests (PCRs) confirm the presence of C. burnetii in cattle herds.…”
Section: Introductionmentioning
confidence: 92%